ArtBreak : A Creative Guide to Joyful and Productive Classrooms - Ziff, Katherine K. (Book collections on Project MUSE., 2016)
"Play is the central, universally significant activity of childhood. Self-directed play in which adults have a supporting rather than directing role is critical to the development and well-being of children. Yet as children have their days and nights increasingly scripted and planned for them, opportunities for play have disappeared over the last half century, especially in schools. ArtBreak's innovation lies in its creative framework. Former school counselor, current professor of counseling, and practicing artist Katherine Ziff developed and tested the program over five years, integrating theory and practice from art therapy, counseling, and child-centered education. The result is a choice-based, guided play experience based on the developmental and restorative possibilities of art making. A detailed how-to guide, this book is the flexible and accessible toolbox that teachers, parents, and counselors need to facilitate relaxing, art-based play that allows children to freely explore, plan, and pursue their own interests with adult support. Easy to implement, ArtBreak can be added to the regular routines of classroom, home, therapy office, or other community setting at whatever scale suits space, time, and budget. No art training is required, only a willingness to embark on a play journey with children"--